Highly Efficient Iridium-Catalyzed Production of Hydrogen and Lactate from Glycerol: Rapid Hydrogen Evolution by Bimetallic Iridium Catalysts - Cheong, Yeon Joo; Sung, Kihyuk; Kim, Jin A.; Kim, Yu Kwon; Jang, Hye Young (European Journal of Inorganic Chemistry, 2020)
Mono- and bimetallic iridium complexes involving novel triscarbene ligands were synthesized and applied to the dehydrogenation of biomass-derived glycerol. This resulted in affording hydrogen and lactate with the excellent turnover number (TON; 3,240,000) and turnover frequency (TOF; 162,000 h–1). The triscarbene ligand in a single frame allowed the formation of bimetallic iridium complexes. This induced the cooperative effect of two iridium ions and rendered excellent TONs and TOFs in the production of hydrogen and lactate.
Keywords: Bimetallics; Carbene ligands; Homogeneous catalysis; Hydrogen-evolution; Iridium catalyst; Iridium complex; Lactate; Monometallics; Production of hydrogen; Synthesised; Carbene ligands; Glycerol; Homogeneous catalysis; Hydrogen; Iridium; Lactate